The Relationship of Digital Post-Purchase Brand Touchpoints on Relationship Quality and Self-Brand Connection in the Context of Repurchase of an Automobile - Suthongwan, Surasak (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2020)
The purpose to investigate the effect of dimensions of digital post-purchase touchpoints on the relationship quality and the self-brand connection within the repurchase of the automobile. Survey research with a structured questionnaire was used for collection. The target population was all current users of the medium segment of a passenger car in Thailand. The sample of this study was male and female, age 18-60 years old, living in Bangkok and its vicinities who bought Toyota Camry or Honda Accord between 2014 and 2018. Factor analysis was used to classify digital post-purchase touchpoints into dimensions. SEM was used to test the relationship between types of digital post-purchase touchpoints and relationship quality, as well as self-brand connection. The rotated solution yielded 3 interpretable factors which includes information-based, interaction-based, and service-based digital post-purchase touchpoints. Structural equation modelling (SEM) indicated that the model was a good fit to data. The predictor were able to account for 15% of the variance in relationship quality, whereas it accounts for 8.5% of the variance in self-brand connection. Interaction-based and service-based digital post-purchase touchpoints have effects on relationship quality and self-brand connection. However, information-based digital post-purchase touchpoints didn’t have a direct effect on relationship quality and self-brand connection.